Why does your pain never get better? Stigma and coping mechanism in people with sickle cell disease - Carvalho,Evanilda Souza de Santana (2021)
ABSTRACT Objectives: to analyze the characteristics of stigma in the interactions of people with pain and sickle cell disease and the coping strategies adopted. Methods: qualitative study, conducted in Bahia’s reference units between January and July 2018. In-depth interviews were applied to 25 adults, followed by content analysis and interpretation in light of the Sociological Theory of Stigma. Results: four categories emerged from the data: Stigma in interactions with family members; Stigma in interactions with people in the general public; Stigma in interactions with health workers; and Strategies for coping with stigma. Final Considerations: in the participants’ interactions, stigma produced discrediting pain reports, labeling and stereotyping, blaming patients for not improving their health, discrimination, racism, inadequate pain assessment, and delay in care. Coping included silencing, covering up, aggressive behavior, exposure to risk, reading religious texts and praises, and church attendance.